Illuminating Leonardo : a festschrift for Carlo Pedretti celebrating his 70 years of scholarship (1944-2014) - Pedretti, Carlo; Moffatt, Constance J.; Taglialagamba, Sara (Leonardo studies., 2015)
Illuminating Leonardo opens the new series Leonardo Studies with a tribute to Professor Carlo Pedretti, the most important Leonardo scholar of our time, with a wide-ranging overview of current Leonardo scholarship from the most renowned Leonardo scholars and young researchers. Though no single book could provide a comprehensive overview of the current state of Leonardo studies, after reading this collection of short essays cover-to-cover, the reader will come away knowing a great deal about the current state of the field in many areas of research. To begin the series, editors Constance Moffatt and Sara Taglialagamba present an impressive group of essays that offer fresh ideas as a departure point for future studies. Contributors include Andrea Bernardoni, Pascal Broist, Alfredo Buccaro, Francesco Paolo di Teodoro, Claire Farago, Francesca Fiorani, Fabio Frosini, Sabine Frommel, Leslie Geddes, Damiano Iacobone, Martin Kemp, Matthew Landrus, Domenico Laurenza, Pietro C. Marani, Max Marmor, Constance Moffatt, Romano Nanni, Annalisa Perissa-Torrini, Paola Salvi, Richard Schofield, Sara Taglialagamba, Carlo Vecce, Alessandro Vezzosi, Marino Viganò, and Joanna Woods-Marsden.